Generalized ISI index of certain families of nanostar dendrimers. Issue 7 (3rd October 2021) - Bharali, Ankur; Pegu, Aditya; Buragohain, Jibonjyoti; Deka, Budheswar
Abstract: A topological index can be considered as the transformation of chemical structures into a real number. The study of molecular structures with the help of topological indices has an important role in the field of chemical graph theory. Dendrimers are chemical compounds which are highly-branched star-shaped macromolecules with nanometer-scale dimensions and have huge range of applications in almost all branches of chemistry. In this work, we calculate the generalized ISI index of certain families of Nanostar dendrimers.